"نمذجة تقلبات أسعار الغاز في الأسواق الدولية من 2015 -2022 " - أحمد, بقاص; طارق, بن علي; الطاهر, بن علي (University of eloued جامعة الوادي, 2022)
"تتنوع وتتزايد إستعمالات الغاز الطبيعي بحيث يمكن القول أن الغاز الطبيعي قد أصبح قرينا إلى حد بعيد لعملية التنمية بالبلاد بمفهومها الشامل اقتصاديا واجتماعيا وبيئيا، وأن الدور المتميز الذي يؤديه الغاز الطبيعي في خدمة الاقتصاد الوطني سوف يستمر بل يتعاظم في المستقبل المنظور لخدمة الأجيال القادمة. وأن ذلك يجيء نتيجة للجهود المتواصلة والإستراتيجية المتكاملة التي أرستها الحكومة الجزائرية بالتعاون مع الشركة الوطنية سوناطراك ووضعتها موضع التنفيذ وقامت على تطويرها الدائم بما يعكس الإدراك المبكر لأهمية وحيوية دور الغاز الطبيعي في الحاضر والمستقبل. وتحتل عمليات الاستكشاف والتنقيب وتنمية الاحتياطي من الغاز الطبيعي في هذا القطاع أهمية ضمن السياسة الطاقية الجديدة، وترمي الأهداف الأساسية المسطرة في مجال الطاقة على المدى المتوسط والبعيد إلى زيادة رفع احتياطي الغاز الطبيعي وتحسين شروط وظروف استغلالها وهذا بإنعاش وتكثيف جهود البحث والاستكشاف بالإضافة إلى تطوير المكامن المكتشفة وغير المستغلة مع تحسين معدلات الاستخلاص في المكامن المستغلة، لينتج عن هذه الأهداف زيادة في الاستهلاك الإجمالي للغاز الطبيعي سواء كان موجه للتصدير أو الاستهلاك الداخلي، وإن أهم ميزات استعمال الغاز الطبيعي أنه أدنى تكلفة من المنتجات الطاقية الأخرى وأقل تلويثا للبيئة، وإن ارتفاع الاستهلاك الداخلي للغاز الطبيعي يرجع إلى تطور صناعات الطاقة ( مصانع الغاز الطبيعي ومحطات توليد الكهرباء) وارتفاع حجم صادرات الدول العربية من الغاز الطبيعي يرتبط بالقدرة الإنتاجية وشبكة التوزيع، من أجل ذلك تقوم هذه الدول بتدعيم قدرتها الإنتاجية عن طريق إنجاز مركبات جديدة وأنابيب تمويل خارجية للغاز وإن تشجيع الاستهلاك الحاضر على حساب الاستهلاك المستقبلي سيضر بالحصة المتبقية للأجيال. "" The uses of natural gas are diversifying and increasing, so that it can be said that natural gas has become closely related to the development process in the country in its comprehensive economic, social and environmental concept, and that the distinguished role that natural gas plays in serving the national economy will continue and even increase in the foreseeable future to serve future generations. And that this comes as a result of the continuous efforts and the integrated strategy established by the Algerian government in cooperation with the national company Sonatrach and put it into practice and based on its permanent development, which reflects the early awareness of the importance and vitality of the role of natural gas in the present and the future. Exploration, exploration and development of natural gas reserves in this sector are important within the new energy policy, and the main objectives set in the field of energy in the medium and long term are aimed at increasing the increase in natural gas reserves and improving the terms and conditions of its exploitation, by reviving and intensifying research and exploration efforts, in addition to developing the discovered reservoirs. The unexploited and untapped rates with the improvement of the extraction rates in the exploited reservoirs, resulting in these objectives an increase in the total consumption of natural gas, whether it is directed to export or internal consumption. Natural gas is due to the development of energy industries (natural gas factories and power plants) and the increase in the volume of Arab countries’ exports of natural gas linked to the production capacity and the distribution network. For this reason, these countries are strengthening their production capacity by implementing new vehicles and external financing pipelines for gas, even if the current consumption is encouraged. At the expense of future consumption will harm the remaining share of generations. "
ماستر تجارة دولية
Keywords: أسعار الغاز الطبيعي – إحتياطي الغاز الطبيعي- إستهلاك الغاز الطبيعي.; natural gas prices - natural gas reserves - natural gas consumption